Sex Differences in Social Cognition and Association of Social Cognition and Neurocognition in Early Course Schizophrenia - Kubota, Ryotaro; Okubo, Ryo; Ikezawa, Satoru; Matsui, Makoto; Adachi, Leona; Wada, Ayumu; Fujimaki, Chinatsu; Yamada, Yuji; Saeki, Koji; Sumiyoshi, Chika; Kikuchi, Akiko; Omachi, Yoshie; et al. (Frontiers in Psychology, 2022)
Background: Both impairment and sex differences in social cognition and neurocognition have been documented in schizophrenia. However, whether sex differences exist in the association between social cognition and neurocognition are not known. We aimed to investigate the contribution of areas of neurocognition to theory of mind (ToM) and hostility bias, representing social cognition, according to sex in early course schizophrenia. Methods: In this cross-sectional study, we assessed neurocognition using the Japanese version of the Brief Assessment of Cognition in Schizophrenia (BACS) and assessed the ToM and hostility bias subdomains of social cognition using the Social Cognition Screening Questionnaire (SCSQ) in 131 participants (65 female, 66 male) diagnosed with schizophrenia within 5 years of onset. Sex differences were analyzed using t-tests. The associations of neurocognitive subdomains with ToM and hostility bias according to sex were analyzed using multiple regression analysis. Results were adjusted by age, estimated premorbid intelligence quotient, and symptomatology. Results: No sex differences were found in ToM (p = 0.071) or hostility bias (p = 0.057). Higher verbal fluency was significantly associated with higher ToM in females (p < 0.01), whereas higher executive function was significantly associated with higher ToM in males (p < 0.05). Higher verbal fluency was significantly associated with lower hostility bias in females (p < 0.05), whereas neurocognition and hostility bias were not significantly associated in males. Conclusion: The results suggest that neurocognition associated with social cognition differ according to sex. These differences should be considered for more effective treatment of social cognition.